ANALISA TEKNIK PENGUKURAN KEPUASAN PELANGGAN PADA PT GRAMEDIA ASRI MEDIA (REGIONAL I TB.GRAMEDIA BALEKOTA) - Joko Hardono; Henri Ponda; Devi Setyaningsih (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2019)
This research proposes Analysis of Customer Satisfaction Measurement Techniques At PT Gramedia Asri Media (Regional I TB.Gramedia Balekota) the purpose of this research is to find out what aspects are used by PT. Gramedia Balekota to assess customer satisfaction and analyze customer satisfaction assessment techniques applied by PT. Gramedia Balekota at this time. The research method used in this study is the method of observation, interview, questionnaire, and literature study. Comparing the current method to Servqual Method with five aspects of customer satisfaction, namely Tangible, Reliability, Responsivenessi, Assurance, and Empaty. From the results of questionaire satisfaction of TB customers. Gramedia Period period January 2018-May 2018 obtained results A total of 189 respondents gave an assessment of Sad Emoticon, a total of 205 respondents gave an Emoticon flat rating, and as many as 106 respondents gave an assessment of Smile Emoticon. The aspect of customer satisfaction assessment included in TB. Gramedia Balekota in it’s questionnaire to measure customer satisfaction. TB.Gramedia Balekota only uses three indicators, namely product availability, shopping convenience, and product quality. Product availability and product quality enter the tangible aspect. And the convenience of shopping goes into the Reliability aspect. So that in measuring the satisfaction of TB customers, Gramedia Balekota has not fulfilled the five aspects of service quality.Key words : Measurement, customer satisfactions, Servqual Method , service quality